2015
DOI: 10.1093/jmcb/mjv005
|View full text |Cite
|
Sign up to set email alerts
|

mTOR signaling promotes stem cell activation via counterbalancing BMP-mediated suppression during hair regeneration

Abstract: Hair follicles (HFs) undergo cycles of degeneration (catagen), rest (telogen), and regeneration (anagen) phases. Anagen begins when the hair follicle stem cells (HFSCs) obtain sufficient activation cues to overcome suppressive signals, mainly the BMP pathway, from their niche cells. Here, we unveil that mTOR complex 1 (mTORC1) signaling is activated in HFSCs, which coincides with the HFSC activation at the telogen-to-anagen transition. By using both an inducible conditional gene targeting strategy and a pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 48 publications
4
66
2
Order By: Relevance
“…A similar phenotype has also been noted in Loeys-Dietz syndrome in humans, characterized by a net increase in TGF-β signaling (59). Notably, mTORC1 inhibition by rapamycin or silencing of Rptor can induce phosphorylation of SMAD3 or SMAD1/5/8 in normal or tumorigenic prostate epithelial cells (80,81) and hair follicle stem cells (60). However, a conclusive mechanism linking mTORC1 loss of function to TGF-β/BMP signaling has been elusive.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…A similar phenotype has also been noted in Loeys-Dietz syndrome in humans, characterized by a net increase in TGF-β signaling (59). Notably, mTORC1 inhibition by rapamycin or silencing of Rptor can induce phosphorylation of SMAD3 or SMAD1/5/8 in normal or tumorigenic prostate epithelial cells (80,81) and hair follicle stem cells (60). However, a conclusive mechanism linking mTORC1 loss of function to TGF-β/BMP signaling has been elusive.…”
Section: Discussionmentioning
confidence: 57%
“…However, the prediction that TGF-β signaling was activated with Rheb cKO was intriguing given that TGF-β is a well-known upstream activator of ROCK signaling (57), and mice and humans with aberrant TGF-β activation in the skin have a thin, translucent epidermis similar to that seen with the Rheb-cKO mice (58,59). In addition, some previous studies have suggested that mTORC1 may inhibit the related BMP signaling pathway in murine skin (60). and suppress desmosomal protein expression (DSP1/2, DSG1, DSG3, and PKP3) in WT keratinocytes (Supplemental Figure 4H).…”
Section: Resultsmentioning
confidence: 81%
“…mTORC1 also appears to play a critical role in the activation of SC proliferation during regenerative episodes in various systems: short term induction of AKT promotes HSC pool expansion (Kharas et al, 2010), while in a mouse model of muscle injury, mTORC1 activation is necessary to allow rapid proliferation of muscle SCs (MuSCs) by promoting a switch from the G 0 to a mTORC1-dependent ‘G alert ’ state (Rodgers et al, 2014). During hair regeneration, mTORC1 signaling promotes hair follicle SC activation by repressing BMP signaling (Deng et al, 2015b). …”
Section: Introductionmentioning
confidence: 99%
“…mTOR is formed by two separate protein complexes, mTOR complex 1 (mTORC1) and mTOR complex 2 (mTORC2), and RPM has generally been believed to interact with mTORC1 but not mTORC2 [1, 16, 17]. However, prolonged treatment of some cell lines with RPM results in reduced levels of mTORC2, as well as decreased phosphorylation of Akt Serine 473, the downstream target of mTORC2 [6, 18, 19].…”
Section: Introductionmentioning
confidence: 99%